Zagraniczna polityka energetyczna Niemiec: uwarunkowania - cele - instrumenty - Molo, Beata (Rocznik Polsko-Niemiecki, 2021)
The paper presents selected issues of German foreign energy policy in terms of determinants-goals-instruments. The factors taken into account in the process of creating foreign energy policy are discussed: the structure of primary energy consumption and of domestic production, the degree of dependence on energy imports and of diversification of supply sources, diversification of transport routes and import infrastructure. The development and goals of foreign energy policy were presented as well as the main instruments for the implementation of energy interests in bilateral and multilateral cooperation were indicated. The problem of defining foreign energy policy was also researched.